Simulação de válvulas em regime não permanente para sistemas de abastecimento - MORAES, Maykon Fernando de (2017)
This work deals with the continuation of the work developed by Anjo (2008), where the inertial dynamic model was approached in a similar way to the gradient method, a model used by EPANET software. The present work made an approach on some types of valves of extreme importance in the system of supply and the need of a greater attention for the sizing of the system. From this point the EPANET software was investigated and the parameters used in all the valves in closing or opening maneuvers were discovered. Two other valves with specific operation were analyzed in addition to the mentioned maneuvers, such as the FCV flow control valve. It has the function of controlling the flow in a certain value. The other valve analyzed is the pressure reducer PRV, whose main function is to reduce the pressure to a pre-set value. After the findings of the parameters were applied to the rigid inertial dynamic model (MDIR). Several situations were simulated, such as: opening, closing, flow control and pressure. The results presented showed the transients generated when performing the specific maneuver, thus proving the efficiency in the implementation of these parameters to the method, being now possible the analysis of the transient generated when carrying out maneuvers in the system.